Analisis Faktor Yang Mempengaruhi Return Saham Pada Perusahaan Makanan Dan Minuman Di Indonesia Tahun 2014-2018 - Yoni Syafitri; Mohamad Zulman Hakim (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2020)
This study aims to determine the factors that influence Stock Returns such as Current Ratio, Return On Equity, Debt to Equity Ratio, Net Profit Margin, Long Term Debt To Equity Ratio in food and beverage companies listed on the Indonesia Stock Exchange. This research is a quantitative type because it refers to the calculation of research data in the form of numbers. The variables of this study include the dependent and independent variables. The sample in this study were food and beverage companies listed on the Indonesia Stock Exchange (IDX) in the 2014-2018 period. The sample selection uses the purpose sampling method, with a total of 7 companies during the 2014-2018 period. Data analysis techniques using the Classic Assumption Test, Multiple Linear Regression Analysis and Hypothesis Test, this analysis was carried out with the help of the software program Eviews 9.0. This study shows that the variable Current Ratio, Return On Equity, Debt to Equity Ratio, Net Profit Margin, Long Term Debt To Equity Ratio simultaneously affect stock returns. With a significance level of 0.033668 less than 0.05. and partially Return On Equity has an influence on stock returns, while Current Rati, Debt to Equity Ratio, Net Profit Margin, Long Term Debt To Equity Ratio has no effect on stock returns.